Pengaruh GCG dan Green Accounting terhadap Pengungkapan CSR Dimediasi Kinerja Keuangan - Cindi Fatika; Rina Yuniarti; Mirra Sri Wahyuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to empirically evaluate GCG and green accounting on CSR disclosure mediated by financial performance. The data used in this research is secondary data originating from the annual reports of mining companies listed on the Indonesia Stock Exchange (BEI) for 2012-2022. The number of samples collected using purposive sampling technique was 4 companies. The data analysis technique in the research uses the SEM-PLS program which is processed with WarpPLS 7.0. The research results show that Good Corporate Governance (GCG), which is proxied using the independent board of commissioners variable, has a negative effect on CSR disclosure, , green accounting has a positive effect on CSR disclosure, financial performance cannot mediate the influence of the independent board of commissioners on disclosure. CSR, financial performance cannot mediate the influence of the audit committee on CSR disclosure, financial performance cannot mediate the influence of green accounting on CSR disclosure.